Analysis of export margins: Application in some Central American agricultural chains, period 2000-2016 - Matarrita Lorente, Sebastian (2021)
This article evaluates the export performance of five agri-chains of the Central American countries during the period 2000-2016. The evaluation is carried out with the methodology of export margins, adapted to the context of value chains, which focuses on export relationships, both the extensive and intensive ones. The cases analyzed are two traditional export chains (coffee and sugar), two traditionally oriented to the domestic market (dairy and beef cattle), as well as one chain oriented towards international markets (pineapple). Additionally, three scenarios were designed in order to shed light on which agri-chains the countries of the region stand out, in which position of the chain emerge the best performing exports, and how important is intra-regional trade compared to exports with the rest of the world. The results show that in the agri-chains analyzed, the exports of their primary products were the ones that performed the best throughout the chain. Products as raw sugar, green coffee and pineapple were great sources of value creation and their success in international markets was largely due to their ability to stay in these. On the other hand, processed products have not expanded in as many markets as primary products and, therefore, year after year the entry to new destinations weighed more on these products.